The project management tool kit 100 tips and techniques for getting the job done right - Kendrick, Tom (AMACOM American Management Association, 2010)
The tools you need for success with every project!
Includes index.
"Includes processes from all of the areas outlined in the Project Management Institute (PMI) PMBOKr Guide, 4th edition (2008)"--Introd. to the 2nd ed.
Keywords: Project management -- Outlines, syllabi, etc.; elektronické knihy; electronic books